Decomposition of urban temperatures for targeted climate change adaptation. (March 2019) - Hertel, Daniel; Schlink, Uwe
Abstract: For the neighbourhood scale a decomposition of the urban heat island (UHI) intensity ( Δ T ) into its contributing processes is suggested. The approach translates individual terms of the energy balance (radiation, evapotranspiration, heat storage, and convection) into temperature increments. This is exemplified using micrometeorological simulations (ENVI-met) for the quarter "Bayerischer Bahnhof" in Leipzig, Germany, under different wind conditions. In result heat storage and convection provide the principal contributions to UHI. The mapping of Δ T -contributions in a neighbourhood is a new tool facilitating the development of tailored measures for reduction of and adaptation to urban heat. For example, the Δ T -contributions (-6.8, -2.6, -9.2, and 15.7 K, respectively) calculated for a courtyard compensate each other. Applying this decomposition at each individual location, suitable adaptation measures can be developed. Considering the superposition of all local Δ T -contributions can support a cost-benefit analysis creating optimal recommendations for city planners. Highlights: The Urban Heat Island effect (ΔT) is decomposed on a neighbourhood scale into five key contributing factors. The contributions to ΔT are mapped as an assessment tool for city planners. Both storage heat and convection were the dominant drivers to the UHI effect. Urban oasis effects can arise near trees and isolated vegetation. A synopsis of all ΔT contributions at each location within a neighbourhood supports the development of targeted heat mitigation measures.